The analysis of children and youth participation goals in Germany - Danner, Stefan (Socialinė teorija, empirija, politika ir praktika, 2003)
The goals of participation policy of youth and children is presented and analysed in the paper. The first goal is to create the opportunity for the children and youth to implement their civil right to establish themselves. The goal is derived from the idea of democracy. The second goal is to let the children and youth to participate in the establishment of civil society. Also it is important to create the ways to motivate the children and youth. The third goal is to utilise the expertise knowledge. The children and youth are experts in the knowledge of their living conditions. It is argued that the goals do not suit well to each other. The author is looking for the best trade offs.